2020
DOI: 10.18051/univmed.2020.v39.42-46
|View full text |Cite
|
Sign up to set email alerts
|

Duration of diabetes as an important risk factor of microalbuminuria in type 2 diabetes

Abstract: <p class="email"><strong>Background</strong></p><p class="email">Microalbuminuria is the earliest evidence of diabetic nephropathy and a major predictor of end stage renal disease (ESRD). The objective of the study was to determine the influence of several risk factors on the presence of microalbuminuria in type 2 diabetics.</p><p><strong> </strong></p><p><strong>Methods</strong></p><p>This observational cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…As FN is produced by kidney mesangial cells, it was also found that FN in these cells is elevated proportionately in the disease states characterized by mesangial expansion including diabetic nodules (Lee and Choi, 2015). Furthermore, the significant elevation in FN level in T2DM patients with and without DN in our study could be due to connective tissue growth factor (CTGF) because it plays a key role in glomerular alteration in diabetic sclerosis because this mediator stimulates transient actin cytoskeleton disassembly in mesangial cells, high production of FN and mesangial cell hypertrophy (Indriani et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…As FN is produced by kidney mesangial cells, it was also found that FN in these cells is elevated proportionately in the disease states characterized by mesangial expansion including diabetic nodules (Lee and Choi, 2015). Furthermore, the significant elevation in FN level in T2DM patients with and without DN in our study could be due to connective tissue growth factor (CTGF) because it plays a key role in glomerular alteration in diabetic sclerosis because this mediator stimulates transient actin cytoskeleton disassembly in mesangial cells, high production of FN and mesangial cell hypertrophy (Indriani et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…This involves limiting salt intake (under 2,300 mg daily consumption), weight loss in the case of obesity, and staying active (Care, 2019). To reach target blood pressure, a patient-specific treatment strategy must be developed at the time of diagnosis and should be executed along with pharmacologic therapy (Bertsimas et al, 2020;Indriani et al, 2020).…”
Section: Blood Pressure Controlmentioning
confidence: 99%